Prospecting Pine Needles to Develop Smart Materials for Specialty Applications - Ranote, Sunita; Kumar, Kiran; Chauhan, Sandeep; Chauhan, Ghanshyam S. (Indian Forester, 2022)
The use of the modified lignocellulosic materials in frontline technologies is an area of current and future interest. It is both a challenge and opportunity for researchers and technologists to transform the huge renewable green wealth into alternate materials through value addition. The present paper reports synthesis of new whole biomass-based hydrogels derived from a huge renewable forest waste - fallen and dry pine needles of the Himalayas. The synthesized materials have been evaluated as soil binders. This is the first-ever such report in the literature